2022
DOI: 10.1097/mat.0000000000001626
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Noninvasive Respiratory Support in Patients With COVID-19 Requiring V-V ECMO

Abstract: Qamar ahmad ,* adam Green , † abhimanyu Chandel , ‡ James lantry, § mehul desai, § Jikerkhoun simou, § erik osborn , § ramesh sinGh , ¶ nitin Puri, † PatriCk moran , ¶ǁ heidi dalton , § alan sPeir , ¶ and ChristoPher kinG §The impact of the duration of noninvasive respiratory support (RS) including high-flow nasal cannula and noninvasive ventilation before the initiation of extracorporeal membrane oxygenation (ECMO) is unknown. We reviewed data of patients with coronavirus disease 2019 (COVID-19) treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Of 2888 studies identified ( figure ), we selected 123 for full-text review. We included 42 observational cohort studies 13 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 involving 17 449 patients ( table 1 ), predominantly from North America or Europe. We did not identify any randomised controlled trials that met our eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 2888 studies identified ( figure ), we selected 123 for full-text review. We included 42 observational cohort studies 13 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 involving 17 449 patients ( table 1 ), predominantly from North America or Europe. We did not identify any randomised controlled trials that met our eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“… 35 , 36 , 37 , 38 , 39 Studies were judged to be at some risk of bias for confounding adjustment and for statistical analysis and reporting if they did not account for clinically important confounders using either logistic regression or Cox proportional hazards models. 15 , 39 , 44 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 Studies reporting adjusted analyses were judged to be at some risk of bias for statistical analysis 35 , 36 , 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 if they did not adhere to methodological standards set by the PROGRESS guidelines, 19 , 20 , 21 , 22 in particular with regards to a priori selection of clinically important confounders and consideration of an appropriate sample size to minimise potential overfitting. 28 , 76 The composition and methodological quality of individual prediction models for each study and funnel plots used to evaluate for publication bias among variables that were assessed in at least ten studies are included in the appendix (p 36–41 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear if the duration of non-invasive respiratory support before intubation and ECMO, also relates to outcomes. Data from a small retrospective analysis support this concern—patients who received non-invasive respiratory support for ≥ 3 days had poorer outcomes than patients who received non-invasive respiratory support for < 3 days [ 53 ]. Likewise, in the ELSO registry, the later cohort (with higher mortality) was noted to have greater use of non-invasive respiratory support prior to ECMO compared with the early cohort [ 34 ].…”
Section: Clinical Management Of Patients With Severe Covid-19 and Ecmomentioning
confidence: 99%
“…However, this remarkable observation, consistent with lower ECMO survival rates observed by other authors in this setting after prolonged noninvasive oxygenation strategies, 2 needs further confirmation due to some limits of the current study. 1 First, among baseline characteristics, there are no clear biochemical or radiological markers of illness severity, such as static respiratory system compliance, PaO 2 /FiO 2 ratio (PF ratio), D-dimer concentrations, and signs (i.e., pneumothorax or pneumomediastinum) suggestive of barotrauma at CT-scan imaging, collected within 24 hours of patient admission. The lack of triage criteria does not allow the detection of high-risk patients, which most likely benefit from early treatment with V-V ECMO.…”
Section: To the Editormentioning
confidence: 99%